Pengembangan Bahan Ajar Matematika untuk Siswa Kelas V Sekolah Dasar - Dita Nindiawati; M Subandowo; Retno Danu Rusmawati (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
Research on the development of mathematics teaching materials in building space and data processing is designed to be more practical, effective, and easy to understand for Grade V students of SD with the ADDIE model development method. The types of data in this study are: content content validation, design validation, student and teacher response questionnaires, and written test of learning outcomes. The analysis technique uses descriptive analysis then the data is processed by being converted using a predetermined formula. The results of content validation from experts after being converted with a table of achievement levels were obtained 89.09%. The results of the design validation from the expert after being converted with a table of achievement levels were obtained 86.49%. Field trial results after being converted with a table of achievement levels obtained 91.81%. While the written test of learning outcomes was obtained as many as 29 children completed with a percentage of 90.625% of 32 children. From the data and analysis that has been done it can be concluded that the results of the development of mathematics teaching materials for Grade V Semester II Elementary Schools can be used as teaching materials